Origin of modulated phases and magnetic hysteresis in TmB4 - Wierschem, Keola (2016)
We investigate the low-temperature magnetic phases in TmB4, a metallic quantum magnet on the geometrically frustrated Shastry-Sutherland lattice, using coordinated experimental and theoretical studies. Our results provide an explanation for the appearance of the intriguing fractional plateau in TmB4 and accompanying magnetic hysteresis. Together with observation of the bump in the half plateau, our results support the picture that the magnetization plateau structure in TmB4 is strongly influenced by the zero-field modulated phases. We present a phenomenological model to explain the appearance of the modulated phases and a microscopic Hamiltonian that captures the complete magnetic behavior of TmB4.